2020
DOI: 10.3390/info11090447
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Goes Green—The Impact of Social Media on Green Cosmetics Purchase Motivation and Intention

Abstract: In the 21st century, green consumption has risen into a global trend, which inclines cosmetic companies to be more environmental-friendly and to have a larger green product portfolio to satisfy these new consumers’ needs. Social media contributed to this trend, shaping consumers’ attitudes into more environmentally conscious behavior. The present study applied the Theory of Planned Behavior (TPB) to explain the impact of Social Media on consumers’ purchase intention and motivation (altruism and egoism). Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
107
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(172 citation statements)
references
References 79 publications
14
107
1
3
Order By: Relevance
“…However, the findings in the literature are mixed. Several studies have argued that egoism may be positively related to pro-environmental behaviour, especially in cases when green products are perceived to be healthier or safer than non-green products (e.g., [39,40]). Consumers may have health concerns for themselves or for their close family.…”
Section: Effect Of Consumers' Value Orientations On Sustainable Consumption Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the findings in the literature are mixed. Several studies have argued that egoism may be positively related to pro-environmental behaviour, especially in cases when green products are perceived to be healthier or safer than non-green products (e.g., [39,40]). Consumers may have health concerns for themselves or for their close family.…”
Section: Effect Of Consumers' Value Orientations On Sustainable Consumption Patternsmentioning
confidence: 99%
“…For example, Wang and colleagues [37] indicated that altruism motivated daily energysaving behaviours of urban residents in China. In a study about green cosmetics, Pop and colleagues [39] showed that altruism has a positive impact on consumers' attitude towards green cosmetics.…”
Section: Effect Of Consumers' Value Orientations On Sustainable Consumption Patternsmentioning
confidence: 99%
“…In order to take advantage of this opportunity, studies have highlighted the important part that social media plays in molding consumer opinions, influencing attitudes and purchasing decisions [50]. This is very evident in the sustainability space, where social media's role in shaping the consumer's green behavior and purchase intention has been significant [51]. Research has shown that social networks help to encourage environmental behavior [52], while celebrity engagement through social media platforms also influences consumer attitudes toward green products [53].…”
Section: Review Of Topicsmentioning
confidence: 99%
“…In terms of social media's influence on sustainable forms of consumer behavior, social media influencers provide a very effective means of illustrating the benefits of adopting a greener, more sustainable form of lifestyle [59]. More recently, Pop et al examined the impact that social media has on consumers' altruistic and egoistic motivation, as well as their attitudes and subjective norms toward green cosmetics products [51]. Using the theory of planned behavior with prediction of purchase intention as the key component, the study found that social media as a source of information has a clear role in consumer motivation formation and consumers' intention to purchase green cosmetics.…”
Section: Review Of Topicsmentioning
confidence: 99%
“…Featuring a carefully detailed topic, "Social Media Goes Green-The Impact of Social Media on Green Cosmetics Purchase Motivation and Intention" is, to date (February 2021), the most widely quoted article of the Special Issue. Based on the Theory of Planned Behavior (TPB), the authors explore the role of social media in enhancing "consumers' purchase intention and motivation" [4]. The authors elaborate an original model, which is tested with the Partial Least Squares structural equations modelling method.…”
mentioning
confidence: 99%